Association between geriatric nutritional risk index and fecal incontinence in individuals with stroke: mediating roles of systemic immune inflammation index and oxidative balance scores - Xiang, Yian; Zhu, Zhuang; Shi, Qifang; Yi, Kefan (Frontiers in Nutrition, 2025)
BackgroundThis study aims to investigate the association of geriatric nutritional risk index (GNRI) with fecal incontinence (FI) and fecal incontinence severity index (FISI) in individuals with stroke and to explore potential mechanisms underlying this link.MethodsData were from the health examination centers of Lishui Municipal Center Hospital and Shanghai Deji Hospital, with 1906 participants. Multivariate logistic regression models, multivariate linear regression models, and restricted cubic spline (RCS) models were applied to assess the association of GNRI with FI and FISI in individuals with stroke. Subgroup analyses and interaction tests were performed to evaluate heterogeneity. Sensitivity analyses were used to test the robustness of the findings. Mediation analysis was employed to investigate the mediating roles of the systemic immune-inflammation index (SII) and oxidative balance score (OBS).ResultsAfter full adjustment for covariates, GNRI demonstrated a significant linear negative association with both FI (OR = 0.69, 95% CI: 0.53–0.81) and FISI (β = −1.08, 95% CI: −1.81 to −0.83) in individuals with stroke. Subgroup analyses confirmed the consistency of these negative associations across all predefined strata, with significant interaction effects observed for BMI categories, smoking status, household income, and diabetes. The SII and OBS were identified as significant mediators of the association of GNRI with FI and FISI in individuals with stroke. Sensitivity analyses revealed that the association of GNRI with both FI and FISI in individuals with stroke remained robust.ConclusionGNRI has a significant negative linear association with FI and FISI in individuals with stroke, mediated by the SII index and OBS. These results highlight the critical role of anti-inflammatory interventions and antioxidant strategies in mitigating FI risk in individuals with stroke.